Airflow Characteristics Investigation of a Diesel Engine for Different Helical Port Openings and Engine Speeds - Willyanto Anggono; Mitsuhisa Ichiyanagi; Reina Saito; Gabriel J. Gotama; Chris Cornelius; Ryera Kreshna; Takashi Suzuki (Institute for Research and Community Services, Institut Teknologi Bandung, 2021)
Intake airflow characteristics are essential for the performance of diesel engines. However, previous investigations of these airflow characteristics were mostly performed on two-valve engines despite the difference between the airflow of two-valve and four-valve engines. Therefore, in this study, particle image velocimetry (PIV) investigations were performed on a four-valve diesel engine. The investigations were conducted under different engine speeds and helical port openings using a swirl control valve (SCV). The results suggest that the position of the swirl center does not significantly shift with different engine speeds and helical port openings, as the dynamics of the flow remained closely similar. The trends of the airflow characteristics can be best observed during the compression stroke. A higher engine speed increases the angular velocity of the engine more compared to the increase of the airflow velocity and results in a lower swirl ratio of the flow. On the other hand, a higher engine speed leads to a higher mean velocity and the variation of velocity results in a larger turbulence intensity of the flow. Increasing the helical port opening brings a reduction in the swirl ratio and turbulence intensity as more airflow from the helical port disturbs the airflow from the tangential port.